The influence of coaches' professional motivation on characteristics of their activities - Aleksey N. Nikolaev (Saratov State University, 2021)
The necessity to identify motivational factors of the coach's activity components and of the dominant orientation of this activity makes the study relevant. Moreover, the relevance of the research is determined by the need to create the scientific basis for consideration and correction of the leading motives in sports coaching. The objective of the study is to identify the correlation between the motives of the coach's professional activity and characteristics of its success. Presumably, the "bifurcation" of orientations among Russian coaches is the result of the qualitative specificity of the dominant motives. The findings of the empirical study of motivational factors which determine the qualitative side of the sports coaching are presented. The study has been carried out on the sample of coaches working at sports schools in St. Petersburg who specialize in various sports (N = 42, men aged from 23 to 67 years old). The following survey methods have been employed: "Need for Professional Activity" (by G. V. Lozova); "Motives of Professional Activity and its Success" (by A. N. Nikolaiev), "Methodology for Studying the Success of Coaches" (during the preparatory and competitive periods) (by A. N. Nikolaiev). The criteria for evaluating the results of the coaches' work are based on the author's original concept which determines successful realization of the coaches' main functions in sports - those providing athletes' personal development, education, health improvement and competition. Evidently, particular groups of coaches' motives influence only certain characterstics of their activity, particular components of its success. The motives of activity are expressed quite vividly. The research reveals motives of "activity" affecting sports results, and the personality motives influencing the development of athletes. The coaches have either a "competition complex" or an "effective pedagogy" complex. The former includes motives aimed at the activity results, material well-being and social status, and the latter means motives directed at the activity process and communication. The results of the study authorize the selection of coaches in connection with the specifics of the sports organization. Additionally, the research results encourage to use psychological tools to correct the motivation of coaches as well as the prospective coaches.